Exciton coupling in diketopyrrolopyrrole–helicene derivatives leads to red and near-infrared circularly polarized luminescence. Issue 3 (23rd November 2017) - Dhbaibi, Kais; Favereau, Ludovic; Srebro-Hooper, Monika; Jean, Marion; Vanthuyne, Nicolas; Zinna, Francesco; Jamoussi, Bassem; Di Bari, Lorenzo; Autschbach, Jochen; Crassous, Jeanne
Abstract : Helicene-bis-diketopyrrolopyrrole derivatives display strong circular dichroism and red circularly polarized emission originating from exciton coupling chirality. Abstract : Molecular and macromolecular chiral π-conjugated diketopyrrolopyrrole (DPP)–helicene derivatives were prepared and their chiroptical properties examined experimentally and theoretically. Exciton coupling leads to red and near-infrared circularly polarized absorption and luminescence arising from the achiral DPP units in the helical environment, highlighting an interesting synergy between the chiral helicene and the organic dye.